Discovery of possible hepatoprotective components from lychee pulp phenolic extract by online knockout methods. (December 2022) - Jia, Xuchao; Dong, Lihong; Wen, Yejie; Huang, Fei; Chi, Jianwei; Zhang, Ruifen
Abstract: Lychee pulp phenolic extract (LPPE) possessed protective effects against nonalcoholic fatty liver disease (NAFLD), while the specific components concerned were unclear. In this study, twelve major components in LPPE were identified by LC-MS and prepared by on line knockout methods. Two antioxidant methods companied with hepatocyte steatosis assay were used to evaluate the contribution of twelve components to the hepatoprotective effects of LPPE. The identified components include four procyanidins and eight flavonoids, they all play active roles in the oxygen radical absorbance capacity of LPPE, while only B-type procyanidin trimer and quercetin 3- O -rutinoside-7- O -rhamnoside exert positive effects on cellular antioxidant activity of LPPE. Six components including procyanidin B2, epicatechin, two quercetin glycosides, and two procyanidin trimers are considered as contributors to lipid accumulation inhibitory effects of LPPE with B-type procyanidin trimer being identified as the main contributor. All the twelve components were recognized as hepatoprotective components against NAFLD in LPPE. Graphical abstract: Image 1